Enhancing Customer Loyalty through Customer Relationship Management (CRM) Implementation - Samrah, Samrah; Nurkidam, A.; Syam, Muh. Taufiq; Haramain, Muhammad; Asmar, Afidatul (Jurnal Kajian Manajemen Dakwah, 2025)
This study aims to analyze the implementation form and identify the opportunities and challenges of applying Customer Relationship Management (CRM) in an effort to maintain and increase customer loyalty at PT. Ranum Jaya Abadi, a Hajj and Umrah travel agency in Sidrap Regency. The research uses a qualitative approach with a case study method. Data was collected through observation, in-depth interviews with management, staff, and customers, as well as documentation studies. The results show that CRM implementation is carried out through three main stages: identification of customer needs, increasing loyalty through sincere and personal service, and maintaining relationships through sustainable interaction. CRM opportunities lie in the use of digital technology for market mapping, operational efficiency, and service personalization. The main challenges are adaptation to rapid technological changes, data management complexity, and the need for human resource development. This study concludes that CRM implemented with Islamic communication principles (Shiddiq, Amanah, Tabligh, Fathonah) and local Pangngaderreng values is effective in building customer loyalty.